Measurement of body condition in a common carabid beetle, Poecilus cupreus: a comparison of fresh weight, dry weight, and fat content - Knapp, Michal; Knappová, Jana (Journal of insect science (Online), 2013)
Because of its direct consequences on reproductive success, body condition is an often-studied individual trait in insects. Various studies on insects use disparate methods to assess "body condition." However, it is doubtful that the results obtained by disparate methods are comparable. In this study, the body conditions of Poecilus cupreus (Linnaeus) (Coleoptera: Carabidae) from eight sites were compared based on the following commonly used variables: (i) fresh weight, (ii) dry weight, and (iii) fat content. All of these variables were corrected for structural body size. Moreover, the effects of using the following ways of assessing structural body size were examined: (a) one size measurement (length of elytron, which is commonly used in beetles), and (b) three size measurements (length of elytron, width of pronotum and length of hind femur). The results obtained using the various estimations of body condition (i, ii, iii) varied significantly. Therefore, studies employing distinct body measurements to assess body condition are not comparable to each other. Using multiple structural size measurements in body condition analyses is better than the common practice of using only one size measurement. However, in the present study, results provided by both methods differ only slightly. A recommendation on the use of terminology in studies on body condition is introduced.
Keywords: brouci; Animals; tělesná hmotnost; ženské pohlaví; Body Weight; tuková tkáň; Coleoptera; tuky; Fats; Adipose Tissue; Male; mužské pohlaví; zvířata; Female